2023
DOI: 10.3390/ma16114047
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Weaving Wire and Arc Additive Manufactured AZ91 Magnesium Alloy Based on Cold Metal Transfer Technique

Abstract: Based on the cold metal transfer (CMT) technique, a deposited wall of AZ91 magnesium alloy was fabricated by weaving wire and arc additive manufacturing (WAAM), the shaping, microstructure, and mechanical properties of the sample with the weaving arc were characterized and discussed by compared with the sample without the weaving arc, and the effects of the weaving arc on grain refinement and property enhancement of the AZ91 component by CMT-WAAM process were investigated. After introducing the weaving arc, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…This allows for relatively unimpeded slip propagation across an entire colony. Additionally, α colonies are considered to be the microstructural features presenting the longest slip length in the material [ 13 ], resulting in a shorter crack initiation time. As such, the microstructural facets can be considered sheared α colonies.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This allows for relatively unimpeded slip propagation across an entire colony. Additionally, α colonies are considered to be the microstructural features presenting the longest slip length in the material [ 13 ], resulting in a shorter crack initiation time. As such, the microstructural facets can be considered sheared α colonies.…”
Section: Results and Analysismentioning
confidence: 99%
“…The LoF defects tend to extend in the scanning direction. Accordingly, the microstructure exhibits strong directionality, which consequently results in anisotropy of mechanical properties [ 12 , 13 , 14 ]. Lu et al [ 15 ] and Carroll et al [ 16 ] studied the tensile mechanical anisotropy of LAM Ti-6Al-4V, and the results showed that samples along the deposition direction present better ductility, while samples along the scanning direction exhibit a higher strength.…”
Section: Introductionmentioning
confidence: 99%